Educational homogamy, parenting practices and children’s early development - González-Sancho, C; Carlos Gonzalez-Sancho (2014)
This thesis investigates the pattern of parental educational homogamy and its implications for parenting practices and children’s early development in contemporary Britain. At the heart of the thesis lies an interest in the mechanisms behind the intergenerational transmission of educational success and, more specifically, the consequences for children of new patterns of parental resemblance in education. The thesis is composed of three empirical chapters, each of which is concerned with a different outcome: 1) trends in educational attainment and educational assortative mating amongst parental couples; 2) parents’ childrearing values and stimulation-oriented interactions with children; and 3) children’s early cognitive and behavioural skills. The first chapter combines data from four birth cohort studies from 1958, 1970, 1990 and 2000-01 while the second and third chapters rely exclusively on the latter study. The empirical analyses use Log-linear and Diagonal Reference models. With regard to trends in educational assortative mating, the thesis finds that the strength of homogamy increased between 1958 and 1970 to decrease thereafter and remain stable, at its lowest level, throughout the 1990s. Moreover, amongst recent cohorts of parental couples the percentage of unions where mothers are more educated than their male partners equalled that of unions exhibiting the opposite pattern. The findings concerning the dynamics of parenting in heterogamous couples suggest a pattern of female dominance in the attitudinal domain as fathers align with the views that can be expected on the basis of the mother’s level of education rather than their own; however, no significant adjustments between partners are observed in parenting behaviours. Lastly, the thesis finds a positive gradient in the association between parental education and children’s early cognitive and socio-emotional development but little or no support for the hypotheses of differential effects for sons and daughters or gender biases in parental preferences for children. That is, no significant interactions are observed between the gender of children and the impact of parents’ absolute and relative levels of education. Taken together, the findings of the thesis qualify concerns about the increase of educational assortative mating in industrialised societies and its potential consequences for the intergenerational reproduction of inequalities in education.